(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2023)
The article updates the problem of maintaining the ability of the economic system of Ukraine to ensure the reproduction of economic processes during the war and to create conditions for the recovery of the economy in the post-war period. In the context of the stated problem, it is suggested that during the period of restoration of the destroyed production systems of big business, an important place in the processes of creating a positive economic result should be occupied by small and medium-sized businesses – thanks to their ability to quickly respond to external threats and find ways to meet public needs even in extreme conditions. In order to confirm the author’s position, the structure of the entrepreneurial sector of the Ukrainian economy was analyzed in terms of the number of participants and the results of their activities in the pre-war period. Among them, service enterprises are singled out, with the selection of those that shape the quality of life of the population and are mainly of an individualized nature (household services, education, medicine, sports, physical rehabilitation, entertainment, tourism, food, etc.) and those that form the service infrastructure of the economy, serving production sectors. The conditions and results of the activity of individual groups of service enterprises from the positions of their tasks in the structure of the national economy and in the global economic space have been studied. With the application of methods of economic and statistical analysis, the share and contribution of entrepreneurs-individuals in the overall results of economic activity was highlighted, and conclusions were drawn using the methods of logical generalization about the conditions and opportunities of service enterprises to increase the development potential and strengthen the competitive positions of domestic industrial producers on the world market in the conditions of war and postwar period. It is noted that in order to increase these opportunities in the current state of the economy of Ukraine, a rethinking of the relationship between the state and business is necessary. The state should become an institution responsible for progress, purposefully increasing opportunities for the development of entrepreneurship as a driving force of progress. On the basis of the author’s vision of the main advantages and weak points of entrepreneurship in its small forms, the possibilities of mutual reinforcement of the effectiveness of the interaction of the state and the entrepreneurial environment and the place in these processes of service enterprises are shown. The need for institutional support for the development of service enterprises capable of increasing the consumer value of the products of industrial producers is emphasized.